(untitled) (Nepalese Journal of Development and Rural Studies, 2019)
This library based paper presents potentiality of agro-tourism in Nepal from rural development perspective. In doing so, focuses are given to fundamentals and management of agro-tourism as well as interface between agro-tourism and rural development. This paper argues that agro-tourism not only emphasizes on good health and environment protection but also creates economic opportunities to the poor farmers, unemployed youths and women. That is why Tourism Vision 2020, Tourism Policy 2007 and National Tourism Strategy Paper (2018-34) have given more focused on rural tourism in general and agro-tourism in particular. However, there are many challenges such as proper management of agro-tourism farms, road accessibility, better health care facilities and evidence based policies related to organic farming and agro-tourism marketing. Finally, this paper suggests performing different activities such as garden visit, harvesting and farm stay, farm restaurants, leisure fishing, highway landscape, agro-diversity conservation and marketing of local organic products for developing and promoting agro-tourism in more potential destinations.